GRI 300 as a measurement tool for the United Nations sustainable development goals: assessing the impact of car makers on sustainability. Issue 1 (2nd January 2021) - Ordonez-Ponce, Eduardo; Khare, Anshuman
Abstract : Research shows a gap in understanding management systems to demonstrate business contribution to sustainability. While businesses have struggled to incorporate sustainability into their strategies, the Sustainable Development Goals (SDGs) represent a useful framework towards new business models for sustainability. This article fuses information from the motor vehicle and parts industry's environmental reporting and how these contribute to the SDGs. Results highlight the GRI 300  s as a useful measurement tool to operationalise the SDGs. We conclude that the industry is not isomorphic, highlighting three subgroups of companies with a large percentage not reporting on any of the standards with differences among companies and countries of origin. Energy and emissions are the standards most reported contributing to SDGs on energy, industry, cities, and climate, while the least reported are water and effluents, and biodiversity, highlighting challenges for the industry on their impacts on water, cities, and the marine and terrestrial species.